Forage Quality Assessment of Herbaceous Species at Benhama, Kashmir - Raja, Azeem; Zaffar Geelani, Syed Naseem; Mughal, Arshid H.; Raja, Tariq A. (Indian Forester, 2023)
Grasses range from extremely persistent long-lived perennials to short lived annuals completing their live cycles, opportunistically, between the onset of rains and the dry season. Determining the nutritional value of forages is important in livestock nutrition, because effective livestock production is related to the amount of nutrients in the forage. The present study was carried out to analyze nutrient of selected forage species in the Faculty of Forestry, SKUAST-Kashmir, Benhama village (Tehsil-Lar, District-Ganderbal). The study identified 9 herbaceous species in their three phenological stages (vegetative, flowering and seeding). The vegetative phase was found to be the best phase in terms of nutritive value. These findings may help the forest managers to schedule grazing in order to coincide the grazing with the most nutritive stage of these species i.e. vegetative stage.